TEKNIK KONTROL SLIDING MODE UNTUK AUTOPILOT ROKET - Rika Andiarti (Jurnal Teknologi Dirgantara, 2006)
This paper deals with autopilot for rocket tracking problem by using sliding mode controller. Rocket model is considered as a linear system with two control input; wing and tail deflection. Simulation results show that the controller effectively works and gives desired performance (fast reaching and low chattering). Keywords: Autopilot, Roket, Tracking, Kontrol, Sliding mode.